A suspensão de segurança, o dispositivo biopolítico em Agamben e os povos indígenas afetados pela construção de Belo Monte - Sampaio, Thayse Edith Coimbra (2019)
This research is concerned with the institutional violence that leads native peoples to bare life, especially the Indians affected by the construction of the Belo Monte hydroelectric power plant. In this space, determined by the Xingu river bus in Pará, there is irreversible damage to the people who traditionally inhabit the area, especially those located in the region called Volta Grande. This takes place in a zone of conflicts, permeated by divergent interests, such as respect for cultural autonomy and conditions for national progress. This context reaches the legal universe and rescues the use of a procedural incident, called suspension of security. This resource materializes an exceptional situation for the autochthonous, as it suspends its rights to the detriment of the economic order or energy security of the country. All the deepening of the discussion is based on theorists of the contemporary philosophy, starting from conceptual fragments like: apparatus, force of law, iustitium; naked life, camp, flock, witness and People - people. Intermediation is operated by anthropology, through such names as Darcy Ribeiro and Pierre Clastres. Therefore, the starting point of this scientific investigation is the "suspension of security". This choice is justified by the alert that awakens in the indigenista thematic, leading the natives to a normative void. Thus, the application of the institute of the security suspension, by national courts of justice, in cases involving native peoples affected by the construction of Belo Monte, integrates the "device", figure of Agamben thought? The methodological itinerary is Foucault's discursive analysis, since it responds to the objectives of this study, by allowng to understand how certain truths are formulated within the judicial discourse, especially if the apparatus under examination corresponds to a control procedure. The results point to the confirmation of the problems raised. This procedural instrument surrounds the natives in a field uninhabited by Law, in which the most absolute inhuman condition occurs. In it they are subject to physical and cultural death and experience constant processes of (de) subjectivation that direct them to the construction of the generic Indian.